Expanding the Chemical Diversity of the Antitumoral Compound Mithramycin by Combinatorial Biosynthesis and Biocatalysis: The Quest for Mithralogs with Improved Therapeutic Window - Méndez, Carmen; González-Sabín, Javier; Morís, Francisco; Salas, José A. (Planta Medica, 2015)
Mithramycin is an antitumor compound of the aureolic acid family produced by Streptomyces argillaceus. It has been used to treat several types of cancer including testicular carcinoma, chronic and acute myeloid leukemia as well as hypercalcemias and Pagetʼs disease. Although the use of mithramycin in humans has been limited because its side effects, in recent years a renewed interest has arisen since new uses and activities have been ascribed to it. Chemically, mithramycin is characterized by a tricyclic aglycone bearing two aliphatic side chains attached at C3 and C7, and disaccharide and trisaccharide units attached at positions 2 and 6, respectively. The mithramycin gene cluster has been characterized. This has allowed for the development of several mithramycin analogs (“mithralogs”) by combinatorial biosynthesis and/or biocatalysis. The combinatorial biosynthesis strategies include gene inactivation and/or the use of sugar biosynthesis plasmids for sugar modification. In addition, lipase-based biocatalysis enabled selective modifications of the hydroxyl groups, providing further mithramycin analogs. As a result, new mithramycin analogs with higher antitumor activity and/or less toxicity have been generated. One, demycarosyl-3D-β-D-digitoxosyl-mithramycin SK (EC-8042), is being tested in regulatory preclinical assays, representing an opportunity to open the therapeutic window of this promising molecular scaffold.
Keywords: Streptomyces argillaceus; Streptomycetaceae; mithramycin; combinatorial biosynthesis; biocatalysis; aureolic acid; mithralog